2009
DOI: 10.3354/esr00146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of finrays as a non-lethal ageing method for protected goliath grouper Epinephelus itajara

Abstract: Currently, there is a conflict between the need to conserve protected fish species and the need to use lethal methods to collect essential biological data, such as age, to assess their population status and recovery trends. We evaluated the precision and accuracy of a non-lethal ageing method for goliath grouper Epinephelus itajara, listed as critically endangered on the IUCN Red List of Threatened Species. Paired finray and otolith samples (n = 21) were collected opportunistically from fish that had died prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…Scales have been a primary structure for nonlethal age determination in many other fish species (e.g., Penttila and Dery, 1988;Welch et al, 1993;Secor et al, 1995;Elzey et al 4 ), but our data support the find- Table 1 Average age and sample size for each type of structure examined for each final age assigned for tautog (Tautoga onitis) collected in Buzzards Bay, Massachusetts, in 2014. Final ages were assigned by 2 age readers taking into account ages assigned, and quality of all structures examined for each fish.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Scales have been a primary structure for nonlethal age determination in many other fish species (e.g., Penttila and Dery, 1988;Welch et al, 1993;Secor et al, 1995;Elzey et al 4 ), but our data support the find- Table 1 Average age and sample size for each type of structure examined for each final age assigned for tautog (Tautoga onitis) collected in Buzzards Bay, Massachusetts, in 2014. Final ages were assigned by 2 age readers taking into account ages assigned, and quality of all structures examined for each fish.…”
Section: Discussionsupporting
confidence: 79%
“…In comparisons of otoliths, dorsal-fin spines, and teeth of the leopard coralgrouper (Plectropomus leopardus), Hobbs et al (2014) found that the most cost-and time-efficient structure for age determination was the dorsal-fin spine. Fin rays or spines also have been found to be useful by Sylvester and Berry (2006) Murie et al (2009) …”
Section: Identification Of a Nonlethal Methods For Aging Tautog (Tautomentioning
confidence: 99%
“…These factors, along with the fact that goliath grouper approaching 6 yr of age and 1 m in length migrate out of the current study area, inhibited our attempts to obtain samples from fish in this size/age category. A study exploring the use of dorsal fin-rays for ageing adult goliath grouper appears in this Theme Section (Murie et al 2009). Studies assessing the utility of fin-rays for ageing other groupers such as gag Mycteroperca microlepis and Nassau grouper Epinephelus striatus are in process (D. J. Murie pers.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantage of using otoliths to age a fish is that it is a lethal method that is not appropriate for critically endangered species. Fortunately, a non-lethal method of aging goliath grouper has been developed using dorsal fin rays (Murie et al 2009). Ages of goliath grouper using otoliths and fin rays from the same individuals were found to be comparable to the age of 18 yr (older individuals were not available) for fish sampled off the east coast of Florida (Murie et al 2009).…”
Section: Atlantic Goliath Grouper Epinephelus Itajaramentioning
confidence: 99%
“…Fortunately, a non-lethal method of aging goliath grouper has been developed using dorsal fin rays (Murie et al 2009). Ages of goliath grouper using otoliths and fin rays from the same individuals were found to be comparable to the age of 18 yr (older individuals were not available) for fish sampled off the east coast of Florida (Murie et al 2009). However, the ability to apply this methodology to age goliath grouper using fin rays or otoliths in French Guiana was uncertain at the outset of this project because of the region's equatorial location, where the seasonal variation is usually minimal and hence the annuli in the aging structures may be indiscernible.…”
Section: Atlantic Goliath Grouper Epinephelus Itajaramentioning
confidence: 99%